2021
DOI: 10.3389/fimmu.2021.754083
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin Dependent Protein Kinase Kinase 2 Regulates the Expansion of Tumor-Induced Myeloid-Derived Suppressor Cells

Abstract: Myeloid-derived suppressor cells (MDSCs) are a hetero geneous group of cells, which can suppress the immune response, promote tumor progression and impair the efficacy of immunotherapies. Consequently, the pharmacological targeting of MDSC is emerging as a new immunotherapeutic strategy to stimulate the natural anti-tumor immune response and potentiate the efficacy of immunotherapies. Herein, we leveraged genetically modified models and a small molecule inhibitor to validate Calcium-Calmodulin Kinase Kinase 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…1A-B, S1A-B) 15,24 . The results from this experiment confirmed that the eGFP reporter is highly active in myeloid cells, especially macrophages 14,16 . In contrast, eGFP expression was not observed in B cells or any T-cell subset (Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…1A-B, S1A-B) 15,24 . The results from this experiment confirmed that the eGFP reporter is highly active in myeloid cells, especially macrophages 14,16 . In contrast, eGFP expression was not observed in B cells or any T-cell subset (Fig.…”
Section: Resultssupporting
confidence: 75%
“…CaMKK2 remains highly expressed in monocytes and monocyte-derived macrophages, and deletion of this kinase attenuates macrophage-mediated inflammatory responses 14 . Recently, we showed that pharmacologic inhibition of CaMKK2 prevents the accumulation of M2-like tumor-associated macrophages (TAMs) 15 while decreasing the number of myeloid-derived suppressor cells (MDSC) in the tumor microenvironment 16 . Thus, CaMKK2 contributes to tumor biology through its ability to regulate cancer cell-intrinsic biology and through its actions in specific myeloid populations [8][9][10][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a different cancer cell-extrinsic role was reported in breast cancer involving the regulation of the anti-tumor immune response through CAMKK2’s functions in macrophages [ 46 ], and more recently in a preclinical model of lymphoma, myeloid-derived suppressor cells (MDSCs) [ 47 ]. While our initial histological analysis did not note any overt changes in tumor immune cell infiltration, more in-depth profiling is required to determine if an immunosuppressive switch is occurring within the prostate cancer tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a different cancer cell-extrinsic role was reported in breast cancer involving the regulation of the anti-tumor immune response through CAMKK2’s functions in macrophages [44] and more recently in a preclinical model of lymphoma, myeloid-derived suppressor cells (MDSCs) [45]. While our initial histological analysis did not note any overt changes in tumor immune cell infiltration, more in-depth profiling is required to determine if an immunosuppressive switch is occurring within the prostate cancer tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%